QUANTIFICATION OF AFLATOXINS IN MAIZE SAMPLES COLLECTED FROM VARIOUS PARTS OF THE PUNJAB, PAKISTAN - M. Manzoor; Z. Farooq; S. Iqbal; H. Mukhtar; M. Nawaz (Journal of Animal and Plant Sciences, 2018)
Maize, one of the main cash crops of Pakistan is cultivated under various ecological conditions. Maize quality deteriorates due to many factors like rainy season, adverse temperature, and traditional practices of harvesting and insufficient storage facilities that stimulate fungal infection (aflatoxins). The present study was designed to quantify the aflatoxins (AFB1, AFB2, AFG1 and AFG2) in maize grains collected from various districts of the Punjab. Seventy two samples of maize grains were collected from 12 districts of Punjab. Toxins were extracted by MycoSep columns ( product code 226) and analyzed by High-Performance Liquid Chromatography ( HPLC) for the quantification of aflatoxin B1 (AFB1), aflatoxin B2 (AFB2) , aflatoxin G1 (AFG1) and aflatoxin G2 (AFG2) . The study showed that AFB1 & AFB2 are the primary contaminants. Out of the analyzed samples, 77.7% of yellow maize grains were contaminated with AFB1, 61.1% AFB2 and 38.8% with high levels of AFG2. The positive samples showed higher than the legal limits as set by the European Union ( EU) , United States Food and Drug Administration (USFDA) Department and Pakistan Standards and Quality Control Authority (PSQCA) . Study further found out that aflatoxin production was mainly caused due to inappropriate storage conditions. Variation in agro-ecological conditions and inappropriate storage cause aflatoxin contamination in maize grains which can be controlled by improvement in the storage conditions and use of proper detoxifying technologies. Fusarium and Penicillium. Contamination of maize with
Keywords: Aflatoxins; Maize grains; HPLC; Food safety.